Analisis Rasio Keuangan Dalam Mengukur Kinerja Keuangan Studi Kasus Pada KSP Kopdit Pintu Air Cabang Kewapante - Martha Renilda; Andreas Rengga; Kristiana Reinildis Aek (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This research aimed to determine the financial performance of the Pintu Air Credit Union of Kewapante Branch assessed based on financial rations. The samples in this research were balance reports and remaining results reports of the Pintu Air Credit Union of Kewapante Branch for the 2017-2021 period. The type of data used was secondary data. Data collection through documentation and interviews. The analysis technique used was the ratio of liquidity, solvency, profitability, and activity based on the Regulation of the Minister of Cooperatives and SMEs of the Republick of Indonesia Number 06/per/M.KUKM/V/2006 concerning guidelines for evaluating cooperatives with achievements or award cooperatives. The results revealed that the financial performance of Pintu Air Credit Union of Kewapante Branch for the 2017-2021 period as a whole had an average performance that was rated D “Not Good”. Meanwhile in each of the 5 years ratio, liquidity was in the category of unfavorable, solvency, and profitability were in the category of good enough, while activity was in the category of very good.